A de novo splice site mutation in CASK causes FG syndrome‐4 and congenital nystagmus. Issue 3 (31st January 2017) - Dunn, P.; Prigatano, G. P.; Szelinger, S.; Roth, J.; Siniard, A. L.; Claasen, A. M.; Richholt, R. F.; De Both, M.; Corneveaux, J. J.; Moskowitz, A. M.; Balak, C.; Piras, I. S.; et al.
Abstract : Mutations in CASK cause X‐linked intellectual disability, microcephaly with pontine and cerebellar hypoplasia, optic atrophy, nystagmus, feeding difficulties, GI hypomotility, and seizures. Here we present a patient with a de novo carboxyl‐terminus splice site mutation in CASK (c.2521‐2A>G) and clinical features of the rare FG syndrome‐4 (FGS4). We provide further characterization of genotype–phenotype correlations in CASK mutations and the presentation of nystagmus and the FGS4 phenotype. There is considerable variability in clinical phenotype among patients with a CASK mutation, even among variants predicted to have similar functionality. Our patient presented with developmental delay, nystagmus, and severe gastrointestinal and gastroesophageal complications. From a cognitive and neuropsychological perspective, language skills and IQ are within normal range, although visual‐motor, motor development, behavior, and working memory were impaired. The c.2521‐2A>G splice mutation leads to skipping of exon 26 and a 9 base‐pair deletion associated with a cryptic splice site, leading to a 28‐AA and a 3‐AA in‐frame deletion, respectively (p.Ala841_Lys843del and p.Ala841_Glu868del). The predominant mutant transcripts contain an aberrant guanylate kinase domain and thus are predicted to degrade CASK's ability to interact with important neuronal and ocular development proteins, including FRMD7. Upregulation of CASK as well as dysregulation among a number of interactors is also evident by RNA‐seq. This is the second CASK mutation known to us as cause of FGS4. © 2017 Wiley Periodicals, Inc.